O desvio aos meios e o discurso do déficit em artigos acadêmicos na perspectiva da linguística de corpus - Kader, Cárla Callegaro Corrêa (Linguagens & Cidadania, 2017)
This work aims to analyze eighty four papers, in the Corpus Linguistics approach, in relation to the presence of means of deviant and/or deficit discourse, according to the Holistic Activity Theory (THA). For this, it was used a corpus with thirty thousand and seven hundred and twenty seven words and the software WordSmith Tools 5.0 for the organization of the Wordlist, the creation of the concord lines (Concord) and the selection of the Keywords. The results, based on the Holistic Activity Theory (THA), reinforce the position of Richter (2008) in relation to the need of regulamentation of the profession of the linguodidactic educator.